2016
DOI: 10.1039/c5cy01681a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding synergetic effects of Zn and Rh–Cr promotion to wide-bandgap Ga, Ta and Ti oxides in photocatalytic water splitting

Abstract: a Promotion of semiconductor metal oxides by specific chemical elements is a widespread approach to enhance photocatalytic water splitting activity. Extraordinary boosting in the activity has been recently reported by Zn (dopant) and Rh-Cr (co-catalyst) promotion to Ga-oxide based photocatalysts. Herein, we report the general applicability of the effectiveness of the promotion strategy used for Ga oxides to Ta and Ti oxides in water splitting under UV irradiation using a slurry reactor. Photophysic characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Thus, nanosized metal particles (i) act as antennas by promoting visible light absorption and (ii) sensitize titanium dioxide by favoring the flux of charge carriers on to the conduction band of the semiconductor in the so-called "Process of Plasmon-Induced Resonance Energy Transfer" (PIRET) [39]. In recent years, a great effort has been recorded among researchers in sensitizing the most widely-adopted metal oxides, such as TiO 2 [40,41], with the aim of employing the visible light range of natural solar light. Nevertheless, "metal-semiconductor" heterojunctions mostly provide photoactivation under light irradiation with wavelengths shorter than 400 nm.…”
Section: Metal-semiconductor Heterojunctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, nanosized metal particles (i) act as antennas by promoting visible light absorption and (ii) sensitize titanium dioxide by favoring the flux of charge carriers on to the conduction band of the semiconductor in the so-called "Process of Plasmon-Induced Resonance Energy Transfer" (PIRET) [39]. In recent years, a great effort has been recorded among researchers in sensitizing the most widely-adopted metal oxides, such as TiO 2 [40,41], with the aim of employing the visible light range of natural solar light. Nevertheless, "metal-semiconductor" heterojunctions mostly provide photoactivation under light irradiation with wavelengths shorter than 400 nm.…”
Section: Metal-semiconductor Heterojunctionsmentioning
confidence: 99%
“…Nevertheless, "metal-semiconductor" heterojunctions mostly provide photoactivation under light irradiation with wavelengths shorter than 400 nm. Amongst recently-developed "metal-semiconductor" heterojunctions with a narrow band gap and band edges suitable for water photosplitting, Pt/PbBi 2 Nb 2 O 9 [42], (V,Rh)/SrTiO 3 [43], (Zn,Rh,Cr)/Ga 2 O 3 [41], (La,Rh,Au)/SrTiO 3 [44], Au/CeO 2 [45], (Mo,Au)/BiVO 4 [46], sulfide-based materials [22], CoO [47] and cadmium chalcogenides [48] have to be noted.…”
Section: Metal-semiconductor Heterojunctionsmentioning
confidence: 99%
“…Photocatalytic activity measurements were performed at room temperature using a home-made continuous reaction system. 18 In brief, the setup consisted of a quartz reactor connected to a gas supply. The reaction products were monitored by an online MS (Pfeiffer Vacuum, Omnistar GSD 320) and the product quantification was verified by a GC (Agilent Technologies, micro-GC 490).…”
Section: Reaction Setupmentioning
confidence: 99%
“…16 For the most active Rh-Cr and Zn codoped Ga2O3 material, the function of Rh-Cr is generally explained as an electron sink whereas the role of Zn is not clear, 17 although we have recently shown that the recombination of charges is greatly delayed by Zn promotion, thus enhancing the life-time of active redox sites and consequently the photocatalytic activity. 18 However, the origin of the promotional effects and detailed insights into the electronic structure of the materials, particularly the synergistic functions of Rh-Cr and Zn co-promotion at an optimum loading of co-catalysts (especially Zn), 14,17 are not known. Since the unique combination of the constituting elements of Rh-Cr/Zn-Ga2O3 catalyst affords outstanding photocatalytic performance in pure water splitting by a few orders of magnitude higher than those generally reported, 14,18 it is imperative to precisely understand the promotional and synergistic effects of Rh-Cr and Zn towards the rational photocatalyst design for hydrogen production from water with sunlight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation